Acaricidal potential of Euphorbia seguieriana and E. helioscopia (Euphorbiaceae) extracts against Tetranychus urticae (Acari: Tetranychidae) - Leila Hemmat-Jou; Shima Rahmani; Marzieh Ghanbari-Jahromi (Persian Journal of Acarology)
Tetranychus urticae Koch (Acari: Tetranychidae) is one of the most dangerous agricultural pests worldwide. Since this mite has the potential to resist a wide variety of chemical acaricides, finding alternative natural sources for its management is suggested. This study estimated the lethal effect of methanol extracts obtained from two Euphorbiaceae plants against female adults after 24 hours using a spray tower. Probit analysis indicated that LC50 values (95% confidence intervals) of Euphorbia helioscopia and E. seguieriana were 4.54 (3.301–6.644) and 11.66 (8.498–21.043) mg/ml, respectively. Phytochemical analysis of both methanol extracts revealed that the total phenolic content, antioxidant rate, and total flavonoid capacity of E. helioscopia were significantly higher than in E. seguieriana (P < 0.05). In addition, HPLC analysis illustrated that rutin and quercetin content in E. helioscopia were 480 ± 0.01 and 2.73 ± 0.01 µg/ml, and in E. seguieriana, those were 230 ± 0.02 and 2.65 ± 0.01 µg/ml, respectively. According to the bioassay results, the methanol extract of E. helioscopia was 2.5 times more harmful than the methanol extract of E. seguieriana. Also, the metabolite contents with toxic activity in E. helioscopia were higher than in the other plant. Therefore, E. helioscopia may have the potential to act as a pesticide against T. urticae.